OPTIMALISASI E-COMMERCE MELALUI TEKNOLOGI WEB MODERN (NEXT.JS, LARAVEL, DSB): SEBUAH TINJAUAN SISTEMATIS LITERATUR (SYSTEMATIC LITERATURE REVIEW) - Yusni Yusni; Supriadi Supriadi; Revalina Revalina; Adelia Asmarani; Nurfadilla Nurfadilla; Dhimas Tribuana (Plexi Digital Indonesia, 2025)
This study aims to analyze the application of modern web technologies in optimizing e-commerce systems through a Systematic Literature Review (SLR) approach. The study was conducted to identify trends, advantages, and challenges in using the Next.js and Laravel frameworks to improve performance, security, and user experience. The research method refers to the PRISMA 2020 guidelines, including the identification, screening, and thematic synthesis stages of 20 relevant scientific articles. The results show that Next.js excels in increasing access speed and search engine optimization through Server-Side Rendering and Static Site Generation, while Laravel plays a crucial role in security, database management, and Model–View–Controller (MVC) architecture efficiency. The combination of the two results in a Headless Commerce approach that separates the front-end and back-end, making the system more flexible, secure, and easily integrated with other technologies such as payment gateways, chatbots, and artificial intelligence. In addition, the implementation of a Netfilter-based security system has been proven to prevent more than 80% of network attacks on e-commerce platforms, while the integration of AI chatbots improves customer service efficiency. In conclusion, the implementation of a modern web framework combined with AI technology and adaptive security systems is able to support the development of innovative, efficient, and sustainable e-commerce in the digital era..